2005
DOI: 10.2147/nedt.1.2.135.61051
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of depression in Parkinson?s disease

Abstract: AimsTo discuss the current methodological and conceptual difficulties inherent in characterizing the emotional manifestations of neurodegenerative disease through critically reviewing depression as a manifestation of idiopathic Parkinson’s disease (PD).MethodsSelective literature review of the neurobiological, psychological, and physical basis of depressive symptoms in PD from 1993–2003, with reference to key earlier articles.ConclusionsThere are difficulties in defining the syndromes of PD itself as well as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Despite the widespread adoption of Mask R-CNN, we found this algorithm did not perform exceptionally well in our study. Our results suggest that this is due to dense cell fields with overlapping bounding boxes, a feature known to corrupt the training process and produce poor network outputs for Mask R-CNN 44 . By contrast, the StarDist network makes robust predictions, but it fails to assemble accurate cell masks because the cells in our dataset are not well approximated by star-convex polygons 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Despite the widespread adoption of Mask R-CNN, we found this algorithm did not perform exceptionally well in our study. Our results suggest that this is due to dense cell fields with overlapping bounding boxes, a feature known to corrupt the training process and produce poor network outputs for Mask R-CNN 44 . By contrast, the StarDist network makes robust predictions, but it fails to assemble accurate cell masks because the cells in our dataset are not well approximated by star-convex polygons 26 .…”
Section: Discussionmentioning
confidence: 95%
“…It is possible then that depression among those with or at risk of PD may be represented by outcomes other than major depression, such as depressed mood. Consideration to a broader interpretation of depression among those with PD has been suggested [23]. …”
Section: Discussionmentioning
confidence: 99%
“…In a study of an Irish family kindred, Khan et al observed dopaminergic dysfunction in the caudate and putamen measured by [ 18 F]-dopa among four subjects with heterozygous parkin mutations, all of whom were asymptomatic [27]. Degeneration of dopaminergic fibers, especially those arising from the ventral tegmental area, has been suggested to be involved in depression [23]. Parkin knockout mice with the exon 7 deletion exhibit cell loss in the locus coeruleus [28] where such loss is postulated to be developmental rather than age-related.…”
Section: Discussionmentioning
confidence: 99%